The MEANING OF FIGURATIVE LANGUAGE FOUND IN JOHN LEGEND'S ALBUM ENTITLED “LOVE IN THE FUTURE” - I Gusti Ayu Vina Widiadnya Putri; I Dewa Ayu Devi Maharani Santika; Miun, Erasmus Roberto (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
Abstract This article discusses about the meaning of figurative language found in John Legend’ album entitled “Love in the Future”. The objectives of this research were to find out types of figurative language and their meanings in John Legend’s song lyrics. The article, entitled “The Meaning of Figurative Language Found in John Legend’s album entitled “Love in the Future”.To analyze the data, the main theory used in this article is first theory proposed by Knickerbocker and Reninger (1963) entitledInterpreting Literature and the second the theory of meaning proposed by Leech (1981) entitled Semantics. This article analyzed the data descriptively by using qualitative method. Thecollected data by browsing and downloading song lyrics from the internet, reading and understanding song lyrics and taking note and classifying the phrase and sentences that contain of figurative language. The data is taken from John Legend’s album entitled “Love in the Future” released in 2013.Type ofmeaning figurative language found in John Legend albumentitled “Love in the Future”are connotative meaning and conceptual meaning. Connotative meaning is the dominant type of meaning found in John Legend’s album.